Optimal time of tumour response evaluation and effectiveness of hypofractionated proton beam therapy for inoperable or recurrent hepatocellular carcinoma - Kim, Tae Hyun (Oncotarget, 2017)
OBJECTIVE: To evaluate the optimal time of tumour response and effectiveness of hypofractionated proton beam therapy (PBT) for hepatocellular carcinoma (HCC). RESULTS: Overall, treatment was well tolerated with no grade toxicity ≥3. Of 71 patients, 66 patients (93%) eventually reached complete response (CR) after PBT: 93.9% (62 of 66) of patients who reached CR within 12 months, and the remaining 4 patients (6.1%) reached CR at 12.5, 16.2, 19.1 and 21.7 months, respectively. The three-year local progression-free survival (LPFS), relapse-free survival (RFS) and OS rates were 89.9%, 26.8%, and 74.4%, respectively. Multivariate analysis revealed that the tumour response was an independent prognostic factor for LPFS, RFS, and OS. CONCLUSION: Most CR was achieved within 1 year after PBT and further salvage treatments in PBT field might be postponed up to approximately 18–24 months. Hypofractionated PBT could be good alternative for HCC patients who are unsuitable for surgical or invasive treatments with curative intent. MATERIALS AND METHODS: Seventy-one inoperable or recurrent HCC patients underwent hypofractionated PBT using 66 GyE in 10 fractions. The tumour responses were defined as the maximal tumour response observed during the follow-up period using the modified Response Evaluation Criteria in Solid Tumors criteria.